Exploring the Role and Opportunities Through Eco Enzyme Making Practices in Implementing Green Accounting in Pematang Kuing Village, Sei Suka District, Batubara Regency - K., Kamilah; Zikra, Silvia Anggraini; Pratiwi, Cici Aulia; Hafizhah, Kayla Nur; Br. Purba, Devia Syahfitri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study delves into the functions and opportunities associated with producing Eco Enzyme as a means of promoting Green Accounting in Pematang Kuing Village, Sei Suka Sub- district, Batubara Regency. Despite the tremendous agricultural potential in this village, there exist challenges in effectively managing organic waste resulting from household activities. By providing educational guidance and facilitating the production of Eco Enzyme, it is anticipated that the community will adopt a more judicious approach to organic waste management. This, in turn, will not only mitigate adverse environmental impacts but also enhance awareness regarding the significance of sound environmental stewardship. Employing a quantitative methodology and regression analysis, this research evaluates the impact of Eco Enzyme production on the implementation of Green Accounting. The findings reveal that despite efforts to heighten awareness and improve waste management practices, the influence on the utilization of Green Accounting remains largely constrained.